Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1590/1982-7849rac20152062
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Calendário e Finanças Comportamentais no Segmento de Fundos Multimercados

Abstract: O objetivo geral deste trabalho consistiu em analisar a relação entre os dias de segunda-feira com a rentabilidade proporcionada pelos fundos de investimentos multimercados brasileiros. A base final de análise foi composta por 3.337 fundos multimercados, totalizando 3.529.808 observações para dados diários, no período de janeiro/2005 a setembro/2013. Com a utilização da análise de regressão com dados em painel, levando-se em consideração variáveis de controle apontadas pela literatura como relevantes, os princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
15

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 44 publications
(53 reference statements)
2
9
0
15
Order By: Relevance
“…These results are partially divergent from those obtained by Jones (2009), because the author identified that smaller funds presented better performance indicators, as well as younger funds. However, other studies already developed in the Brazilian market (Milani & Ceretta, 2012;Milani & Ceretta, 2013;Malaquias & Mamede, 2015) presented results in the same line (size, with positive relation). Better-performing funds also appear to be the ones that charge lower administration and performance fees, as suggested by the results obtained.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…These results are partially divergent from those obtained by Jones (2009), because the author identified that smaller funds presented better performance indicators, as well as younger funds. However, other studies already developed in the Brazilian market (Milani & Ceretta, 2012;Milani & Ceretta, 2013;Malaquias & Mamede, 2015) presented results in the same line (size, with positive relation). Better-performing funds also appear to be the ones that charge lower administration and performance fees, as suggested by the results obtained.…”
Section: Resultssupporting
confidence: 67%
“…The size of the fund has already been used by other studies (Jones, 2009;Milani & Ceretta, 2012;Milani & Ceretta, 2013;Malaquias & Mamede, 2015), there being arguments for a positive relationship between this variable and the profitability of funds in the Brazilian market.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the test variables related to the fund manager, given the di culty of information involving individual managers, proxies had to be created to measure them (Chevalier & Ellison, 1999;Malaquias & Mamede, 2015;Switzer & Huang, 2007). us, the "manager's experience" was calculated in years by the di erence between the base date 1/31/2016 and the date the company managing the fund was founded.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…O estudo das finanças comportamentais enfoca que, por mais que as pessoas tentem a agir com racionalidade, há fatores externos psicológicos e comportamentais que influenciarão no processo de decisão de compra (MALAQUIAS;MAMEDE, 2015 O processo utilizado para atender aos propósitos desta pesquisa pode ser classificado como quantitativo, pois as informações coletadas são abordadas de forma estatística e o fornecimento de dados ocorre de forma mais precisa (HAIR et al, 2005…”
Section: Finanças Comportamentaisunclassified